Perbandingan Sistem Politik dan Kekuasaan Indonesia-Australia - Anggraini, Leni; Hardian, Mirza; Erlande, Rike; Juri (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
This research compares the political systems and power structures of Indonesia and Australia, focusing on their similarities and This study compares the political systems and power structures of Indonesia and Australia using a qualitative approach through a comparative literature review. Indonesia adopts a presidential republic system. In contrast, power in Australia is distributed among the executive, legislative, and judicial branches under a constitutional monarchy (Westminster system) through a parliamentary model. The primary objective of this study is to identify the similarities and differences in democratic practices, the distribution of power, and the level of public trust in state institutions. The findings indicate that both countries share similarities in democratic practices, such as the regular conduct of elections and the implementation of the principle of Trias politica, which divides power into three main branches: the executive, the legislative, and the judiciary. However, notable differences are evident in their governmental structures. In Indonesia, the president serves as both head of state and head of government. In contrast, in Australia, the monarch plays a ceremonial role, while the prime minister, elected through parliamentary support functions as the head of government. There are also differences in terms of tenure. In Indonesia, members of the legislature serve five-year terms, while in Australia they serve three-year terms. Moreover, the Australian prime minister has no fixed term limit, as tenure depends on continued parliamentary support. In Australia, public trust in state institutions is generally higher due to greater transparency, accountability, and more effective law enforcement. Meanwhile, Indonesia faces ongoing challenges such as corruption and public dissatisfaction with the performance of state institutions, which results in comparatively lower levels of public trust.